Factual assumptions on the exclusion of offspring in recent roman rota’s jurisprudence - Guzmán Pérez, Cristina (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
This research shows recent case law developments of the Apostolic Tribunal of the Roman Rota regarding the exclusion of bonum prolis, distinguishing those cases in which the exclusion is complete and perpetual, temporary or ad tempus, ad libitum, as well as the procedural requirements and the most relevant causa contrahendi and causa simulandi invoked and accepted by the Apostolic Tribunal of the Roman Rota from 2006 to 2012.